Kick It: A Social History of the Drum Kit, Matt Brennan (2020). Issue 3 (1st November 2020) - Smith, Gareth Dylan
Review of: Kick It: A Social History of the Drum Kit, Matt Brennan (2020)New York: Oxford University Press, 371 pp., ISBN 978-0-19-068387-0, p/bk, $29.95